CREATIVITY THROUGH SEAL BATIK OF USED CARTONS ON DISABILITIES STUDENTS - Yanuarmi, Dini; Widdiyanti, Widdiyanti; Sundari, Sri (Batoboh, 2019)
The purpose of this community service activity is to provide knowledge (knowledge) and skills (skills) to people with disabilities, especially in the State Extraordinary School 1 of Padangpanjang. This training is also an effort to maintain and preserve the existence of batik as a traditional art and cultural heritage. Making batik techniques from used cardboard is expected to equip students with abilities and expertise so that they have the provision of skills that will improve, develop attitudes, knowledge as a person and community members in conducting reciprocal relationships with the social, cultural and natural environment. The method consist of two stages, namely demonstration and practice. The practice begins with making a design motif that is applied to the canting cap, followed by making batik with the stamp technique. The results are made in the form of tablecloths and bags, with the motif designs from the creations of the students. Limitations do not become a barrier for them in creativity, instead they have the ability to work on taste, intention and creativity that can be seen from the canting cap produced with creative and innovative designs.